Occupational needle stick injuries amongst prehospital emergency medical service personnel in South Africa - McDowall, Jared Ryan (My University, 2019)
Prehospital personnel are frequently exposed to challenging situations that place them at increased risk of sustaining a needle stick injury (NSI). Blood borne infections such as HIV and Hepatitis B or C may be transmitted from a NSI. Sub-Saharan Africa has the largest number of people living with HIV globally. There is no data pertaining to NSI among Emergency Medical Service (EMS) personnel in South Africa. This study aimed to investigate the cumulative incidence, knowledge, attitudes and practices pertaining to NSI’s amongst a select group of prehospital EMS personnel in Johannesburg. Methods: This was a prospective, questionnaire based, cross-sectional survey of personnel employed at three EMS service provider in Johannesburg. Results: Of the 240 subjects that participated in the study, there was a total of 93 NSI’s amongst 63 (26.3%) subjects. Of these, 41 (65.1%) had sustained only one previous NSI, 16 (25.4%) had two previous NSI’s, 5 (7.9%) had three previous NSI’s and one (1.6%) had five previous NSI’s. Almost two-thirds (n=60; 64.5%) of NSI’s were sustained during intravenous line insertion. Most of the study subjects were male (n=145, 60.4%), between the age of 25-29 years (n=67, 27.9%), had a BLS qualification as the highest level of training (n=89, 37.1%), had >10 years of EMS experience (n=69; 28.8%) and were up to date with their Hepatitis B vaccination at the time of the study. HIV post exposure prophylaxis (PEP) was initiated in 82 (88.2%) out of the 93 NSI incidents. However, the recommended 28-day course of therapy was only completed in 68 (82.9%) out of the 82 cases where PEP was initiated. Conclusion: Prehospital personnel are at high risk of sustaining a NSI. There is a need to promote awareness with regards to the risks, preventive measures, awareness of PEP protocols and the timely initiation and completion of HIV PEP amongst EMS personnel in Johannesburg.
A Research Report submitted to the Faculty of Health of the University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Science in Emergency Medicine, Johannesburg, 2019
Keywords: Communicable Diseases